Knowledge, Attitude and Practice Evidence in Digital Environment and Forecasting the Corona Virus Outbreak in the UK, Spain and Belgium - Maryam Moghadami; Abbas Smiley; Ka Wa (International Journal of Digital Content Management, 2020)
Based on Statista reports as of April 7, 2020, there have been 52,624 deaths in Europe due to COVID-19 since the first recorded European death in France on February 15. We compared two models to assess the outbreak of coronavirus in the UK, Spain and Belgium, their healthcare expenditure and the number of hospital beds as two indices of the healthcare system. Base and advance exponential smoothing models were used to forecast the total number of new cases and fatalities in the next 15 days for each of the evaluated countries, with an upper and lower banding. The models were fine-tuned with temporal granularity and an adjust seasonality set to seven days. Furthermore, the study assessed the healthcare capacity of these countries by looking at key metrics at a national level and tried to compare them in a relative term by drawing correlations between the total number of cases and fatalities. In addition, the current study compared the three countries according to the KNOWLEDGE, ATTITUDE and PRACTICE (KAP) system and found the associated similarities. Also, the gaps in KAP on WHO level was appraised. The KAP shortfalls at all levels of international, governmental, organizational and individual levels were recognized. The success of the implementation of any intervention in the prevention of coronavirus epidemics is highly dependent on KAP of people, organizations and governments. Finally, a multicomponent system at international level is proposed to tackle the future infectious pandemics.